DISCOURSE AS AN OBJECT OF LINGUISTIC RESEARCH - Khusanova, Munis (Журнал иностранных языков и лингвистики, 2021)
This article focuses on the origin of the term “discourse” and provides analysis of the term from different perspectives. Apart from it, the author investigates the research of scholars and discourse schools to get deeper understanding of the term.